Asymmetric metal free β-boration of α, β-unsaturated imines assisted by (S)-MeBoPhoz. Issue 5 (19th December 2014) - Cascia, Enrico La; Sanz, Xavier; Bo, Carles; Whiting, Andrew; Fernandez, Elena
Abstract : The adduct [MeO → Bpin–Bpin] − efficiently mediates the β-boration of α, β-unsaturated imines formed in situ . Abstract : The adduct [MeO → Bpin–Bpin] − efficiently mediates the β-boration of α, β-unsaturated imines formed in situ . The use of chiral phosphines as additives, and in particular the chiral phosphine ( S )-MeBoPhoz, enables the catalytic asymmetric reaction to proceed with higher enantioselectivity than the analogue copper(i ) mediated reaction.